Remote check test battery for cochlear implant recipients: proof of concept study. (1st June 2022) - Maruthurkkara, Saji; Allen, Agnes; Cullington, Helen; Muff, Joanne; Arora, Komal; Johnson, Susan
Abstract: Objectives: (1) To investigate the remote check test battery, designed for self-administration by cochlear implant (CI) recipients, parents/caregivers, to determine if the results give adequate information for clinicians to decide the necessity of an appointment and to capture suggestions for improvement. (2) To gauge acceptance of remote monitoring by CI-recipients and their parents/caregivers. Design: Prospective, multicentre, un-blinded, non-randomized, single-subject, repeated-measures evaluation. The test battery includes an implant-site photograph, impedance measurements, datalogs, questionnaires, speech perception and aided threshold tests. Clinicians reviewed test battery results, followed by a clinical appointment with each CI-recipient, and reported if the battery identified all the issues. Study sample: n = 93 CI-recipients (73 adults, 20 children) and 28 clinicians. Results: The test battery identified 94% (615/656) of all issues. The test battery and clinician observations agreed in 99% (92/93) of cases on the need for a clinic visit. For 68% (63/93) of cases, the test battery identified all clinician observed issues. The majority (77%, 72/93) of recipients would be satisfied if clinic visits were based on their test battery results. A significantly high proportion agreed that remote monitoring was more convenient than clinic visits and could result in travel, time and cost reductions. Conclusion: This is the first comprehensive test battery designed for CI-recipient remote monitoring.